Comparative Effect of The Inclusion of Zootechnical Additives in the Feed of Japanese Quails in Two Productive Phases - Lemos, Marina J.; Calixto, Ligia F. L.; Souza, Daniele S. [UNESP]; Reis, Tulio L.; Nascimento, Aparecida A.; Oliveira, Carlos A. (Acad Brasileira De Ciencias, 2018)
This study aimed to evaluate the intestinal morphology, performance and financial analysis of the inclusion of additives in the feed during the productive period of 360 Japanese quails distributed in a completely randomized design in a split plot scheme in time with five treatments and eight repetitions of nine birds each. The treatments were: control, antibiotic, prebiotic, probiotic and synbiotic. The variables were: height, width and width/height ratio of the villi, crypt depth and villus/crypt ratio, feed intake, egg production, egg weight average, egg mass, feed conversion per mass and per dozen eggs and viability, internal rate of return, net present value and cost benefit. The additives in the feed increased height and width of the villi, decreased crypt depth and increased villus/crypt ratio compared to the control. Feed intake was lower after the inclusion of antibiotics and synbiotics in the feed. Egg production and feed conversion improved after the inclusion of additives in the feed compared with the control. The reduction of feed intake was more pronounced with the addition of antibiotic and synbiotic in the final stage of the productive period of the Japanese quails. The inclusion of antibiotics and synbiotic proved to be more financially viable.
Keywords: antibiotic; intestinal morphology; prebiotic; probiotic; symbiotic